Smarana – Thrigirani biddala kosam . Smarana - Remembering Lost Children - Vanaja, C. (Now, 2004)
Verzio FF Submission A film about the agony of the mothers who lost their children in the ongoing Naxalite movement in Andhra Pradesh, India. About a dozen mothers who are essentially non-political and do not necessarily share their deceased children's political views, talk about their memories, the trauma, repression they underwent both physically and emotionally when their children were away from home fighting for others people's causes. Mothers were randomly interviewed from two regions where the movement is intense - the Uddanam area of Srikakulam district and the Jangoan area of Warangal district.